Safety, feasibility, tolerability, and clinical effects of repeated psilocybin dosing combined with non-directive support in the treatment of obsessive-compulsive disorder: protocol for a randomized, waitlist-controlled trial with blinded ratings - Ching, Terence H. W.; Amoroso, Lucia; Bohner, Calvin; D’Amico, Elizabeth; Eilbott, Jeffrey; Entezar, Tara; Fitzpatrick, Madison; Fram, Geena; Grazioplene, Rachael; Hokanson, Jamila; Jankovsky, Anastasia; Kichuk, Stephen A.; et al. (Frontiers in Psychiatry, 2024)
Background: To date, few randomized controlled trials of psilocybin with non-directive support exist for obsessive-compulsive disorder (OCD). Results and participant feedback from an interim analysis of an ongoing single-dose trial (NCT03356483) converged on the possibility of administering a higher fixed dose and/or more doses of psilocybin in future trials for presumably greater benefits. Objectives: This trial aims to evaluate the safety, feasibility, tolerability, and clinical effects of two doses of psilocybin paired with non-directive support in the treatment of OCD. This trial also seeks to examine whether two doses of psilocybin lead to greater OCD symptom reduction than a single dose, and to elucidate psychological mechanisms underlying the effects of psilocybin on OCD. Design: A randomized (1:1), waitlist-controlled design with blinded ratings will be used to examine the effects of two doses of oral psilocybin paired with non-directive support vs. waitlist control on OCD symptoms. An adaptive dose selection strategy will be implemented (i.e., first dose: 25 mg; second dose: 25 or 30 mg). Methods and Analysis: This single-site trial will enroll 30 adult participants with treatment-refractory OCD. Aside from safety, feasibility, and tolerability metrics, primary outcomes include OCD symptoms assessed on the Yale-Brown Obsessive-Compulsive Scale – Second Edition (Y-BOCS-II). A blinded independent rater will assess primary outcomes at baseline and the primary endpoint at the end of the second dosing week. Participants will be followed up to 12 months post-second dosing. Participants randomized to waitlist will be rescreened after 7 weeks post-randomization, and begin their delayed treatment phase thereafter if still eligible. Ethics: Written informed consent will be obtained from participants. The institutional review board has approved this trial (protocol v. 1.7; HIC #2000032623). This trial was also registered with ClinicalTrials.gov (NCT05370911). Discussion: This study seeks to advance our ability to treat refractory OCD, and catalyze future research seeking to optimize the process of psilocybin treatment for OCD through understanding relevant psychological mechanisms.